TATA KELOLA PENYELENGGARAAN MENARA TELEKOMUNIKASI OLEH DINAS KOMUNIKASI, INFORMATIKA, STATISTIK DAN PERSANDIAN KOTA PEKANBARU (STUDI KASUS PADA KECAMATAN TAMPAN) - Siti Khairun Nikmah; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The management of telecommunication towers in Pekanbaru City still raises a number of problems including the large number of illegal and legal towers that affect the aesthetics of Pekanbaru City, the lack of socialization to the community regarding the impact of telecommunication towers, the location of telecommunication towers that have not and regulations, radiation concerns from the number of legal and illegal towers that are quite large in public health. The purpose of this study is to find out how governance and what factors influence the governance of telecommunications tower operations by the communications, informatics, statistics and coding systems of Pekanbaru City. The research method used is a type of qualitative research with a case study method with data collection techniques through interviews, observation, and documentation. The selection of research informants used a purposive sampling technique. The results of this study indicate that there are factors that influence the governance of telecommunications towers by the communications, informatics, statistics and coding systems of the City of Pekanbaru. These factors are insufficient human resources and lack of experts in the field of towers, inadequate facilities and infrastructure and limited funds or budgets.Keywords: Governance, Telecommunication Tower, Management